Increasing Students Learning Outcomes of Fiqih Subject of Class VII MTs Nahdlatul Khairaat Labuan about Shalat Berjamaah lesson through Demonstration Method - Hasbi Rahman (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
This research aims to determine the increasing student learning ability about shalat berjamaah lesson through demonstration method. To answer the questions above, the researcher held class action research using Kemmis and Mc. Taggart design which consist two cycles, and every cycle consist four phases: (1) planning, (2) acting, (3) observation, and (4) reflection. The setting of the research was held in MTs. Nahdlatul Khairaat Labuan who consist 13 men and 7 women. The technique of collecting data was held by test, observation, interview, and documentation. The result of the research showed that student learning outcomes in cycle I the average was 64.38 which percentage was 50%. After doing reflection and some of repairing in cycle II, the student learning outcomes got increasing, which the average was 77.75 and percentage was 100%. The result showed that using demonstration method can increase the student learning outcomes of fiqih subject of class VII MTs. Nahdlatul Khairaat Labuan about shalat berjamaah lesson.